Confinement and Chiral-Symmetry Breaking in the Covariant Spectator Theory - Peña, M. T. (2016)
We show that in the framework of the covariant spectator theory (CST), the equations for the quark anti-quark bound state and for the quark mass function satisfy the requirement of chiral symmetry, incorporating spontaneous chiral symmetry breaking. We then present the results for the pion electromagnetic form factor obtained within a dynamical quark model formulated in Minkowski space and based on the CST.